Exploring the molecular mechanism of EGCG in preventing obesity-induced precocious puberty based on serum metabolomics and molecular docking - Gao, Shiyu; Xia, Lina; Jiang, Chenzhenghao; Shao, Bang; Shao, Ying; Li, Xiaojing; Wu, Peiying; He, Jieyi; Du, Qiujv; Liang, Lingwei; Gu, Qiuyun (Frontiers in Nutrition, 2025)
ObjectiveObesity-induced precocious puberty presents serious health risks to adolescents. Building on our previous finding that epigallocatechin gallate (EGCG) exhibits a preventive effect on obesity-induced precocious puberty, the present study aims to elucidate the underlying molecular mechanisms.MethodsFemale C57BL/6 mice were divided into four groups: control, normal diet + EGCG, high-fat diet (HFD), and HFD + EGCG. Body weight, vaginal opening time, and serum samples were analyzed to assess the effects of EGCG on obesity-induced precocious puberty, using serum metabolomics and molecular docking.ResultsEGCG treatment significantly altered the serum metabolite profile, particularly affecting lipid metabolism. Glycerophospholipid metabolism emerged as the key pathway modulated by EGCG. Molecular docking identified phosphatidylserine decarboxylase, phospholipase D, and phosphatidylserine synthase as potential targets.ConclusionEGCG prevents obesity-induced precocious puberty, an effect associated with the reshaping of lipid metabolism, with key enzymes in the glycerophospholipid metabolism serving as potential therapeutic targets. These findings provide a foundational hypothesis for further mechanistic investigation.